2011
DOI: 10.1159/000324456
|View full text |Cite
|
Sign up to set email alerts
|

Lower Expression of Tight Junction Protein 1 Gene and Increased FOXP3 Expression in the Small Bowel Mucosa in Coeliac Disease and Associated Type 1 Diabetes Mellitus

Abstract: Background: The role of regulatory T cells expressing FOXP3 in the pathogenesis of coeliac disease (CD) and type 1 diabetes (T1D) has been reported. Recent data have placed special focus on the interplay between the intestinal barrier and immunoregulatory processes. We aimed to determine whether the expression of tight junction protein 1 (TJP1), which reflects small bowel mucosa permeability, is changed in CD and T1D. Methods: Transcription levels of TJP1 and FOXP3 genes were evaluated in the small bowel biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 103 publications
0
13
1
Order By: Relevance
“…Children with concomitant T1D and CD have previously been reported to express high levels of IL-1, IL-2, IL-4, IFN-, TNF- FOXP3 [181,197,257,364,390]. This is in contrast to our findings, where Swedish children with both T1D and CD seemed to express similar levels of IL-2, FOXP3 and IL-21 as reference children (unpublished results, data not shown).…”
Section: Mucosal Immune Responses In T1dcontrasting
confidence: 99%
See 1 more Smart Citation
“…Children with concomitant T1D and CD have previously been reported to express high levels of IL-1, IL-2, IL-4, IFN-, TNF- FOXP3 [181,197,257,364,390]. This is in contrast to our findings, where Swedish children with both T1D and CD seemed to express similar levels of IL-2, FOXP3 and IL-21 as reference children (unpublished results, data not shown).…”
Section: Mucosal Immune Responses In T1dcontrasting
confidence: 99%
“…IFN- has been shown to disrupt epithelial barrier function by decreasing the levels of the tight junction protein TJP1, also known as zonula occludence protein ZO-1 (reviewed in [362]) [363]. This is supported by studies showing low expression of ZO-1 in untreated CD patients [359,364,365] and particularly in those with concomitant CD and T1D [364]. It have been reported that treatment with a GFD improved and in some cases normalized the TJP1 (ZO-1) levels [365,366].…”
Section: Type 1 Responses In CDmentioning
confidence: 97%
“…An interesting observation is the similarity in the IgG anti-tTG subclass usage profile between CD and T1DM, two diseases thought to share common pathogenic features such as impaired intestinal mucosal integrity (de Kort et al, 2011), and a shared genetic background (Vorobjova et al, 2011). Certainly the signature antibody responses in both conditions are predominantly IgG1; anti-GAD and IA-2 in T1DM (Bonifacio et al, 1999;Hawa et al, 2000) and anti-tTG and gliadin in CD (Hvatum et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the density of FoxP3 + cells are also correlate with histological grade of atrophic changes in the small bowel [136] . Upregulated FoxP3 expression may counterbalance the loss of mucosal integrity by maintaining immune tolerance in the small intestine of patient with both celiac disease and T1D [137] . Contrary, a low expression of the tight junction protein 1 (TJP1) serving as a marker of intestinal mucosa integrity has been found in patients with both T1D and celiac disease [136,138] .…”
Section: T-regulatory Associated Immunitymentioning
confidence: 99%